RANCANG BANGUN SISTEM PEMBELAJARAN ONLINE BERBASIS MOODLE DI SEKOLAH TINGGI TEKNOLOGI INDONESIA - Mujiono Mujiono; Albert Gifson Hutajulu; Syah Alam (Universitas Tarumanagara, 2021)
The Indonesian College of Technology (STTI) is a private university that has adequate infrastructure in the field of information technology. The face-to-face learning process in class that has been running so far still has weaknesses, plus the covid-19 pandemic makes lectures carried out online. The real problem faced by every STTI lecturer or student is mainly about the attendance of students or lecturers who are unable to attend. The STTI campus which organizes employee class lectures, where at some time you have to leave the city to work on a project, both maintenance and development. Likewise, at one point, a lecturer also has needs outside the city, for example, education and training, seminars and others that cannot be left behind. In this study, the design and construction of an e-learning learning system or digital